Exploring the relationship between built environment and multidimensional street market vitality: Insights from urban villages in Shenzhen using multi-source data - Yueyi Tan; Jusheng Song; Yunxi Bai (PLoS ONE, 2025)
Street markets play a vital role in revitalizing cities, especially within urban villages, which are unique neighborhoods characterized by dense migrant populations and complex social dynamics. This study addresses the underexplored relationship between street market vitality and the built environment, aiming to promote sustainable urban growth and inclusivity. A comprehensive framework embraces both macro-structural and micro-experiential perspectives, integrating urban morphology, functionality, and human perception indicators, to investigate the relationship between multidimensional vitality and the built environment in Shangxia Sha urban village street markets, Shenzhen, China. Utilizing multi-source data, geographic information systems, street view semantic segmentation, and space syntax, the study applies Geographically and Temporally Weighted Regression (GTWR) and Multiscale Geographically Weighted Regression (MGWR) models to explore spatiotemporal and multi-scale spatial heterogeneity. Findings reveal the pivotal role of urban functionality in shaping multidimensional vitality. Specifically, social vitality is most positively correlated with bus convenience and most negatively with street length. In terms of commercial vitality, point of interest (POI) density shows a strong positive relationship, while life service facility density is most negatively associated. This research provides insights into how the living street scenes shaped by low-income and migrant populations interact with the urban environment, offering guidance for fostering urban inclusivity and diverse communities.